Influence of the Hydric State and Lime Treatment on the Thermal Conductivity of a Calcareous Tufa - Mekaideche, K.; Derfouf, F-E. M.; Laimeche, A.; Abou-Bekr, N. (Civil Engineering Journal, 2021)
An experimental study was conducted to investigate changes of thermal conductivity of a raw and lime-treated calcareous tufa (north-west of Algeria) during drying process. Treated (with 4% of lime) and untreated samples were prepared by static compaction at the Standard Proctor Optimum (SPO), Modified Proctor Optimum (MPO) and at a constant stress level of 4 MPa. Transient Hot Wire (THW) method was used to measure the thermal conductivity and the water content and degree of saturation of samples were determined at various drying times. Results show that the drying process induces a decrease in thermal conductivity. This parameter seems to vary linearly with the water content and the degree of saturation. In addition, it was found that the lime treatment leads also to a decrease in the thermal conductivity. Thus, the drying process and the lime treatment will jointly contribute to the reduction of the thermal conductivity of the studied material in such a way that it is more insulating than some traditional building materials like concrete or fired bricks.Â Doi: 10.28991/cej-2021-03091663 Full Text: PDF